Prevalence and characterization of ESBL-producing Escherichia coli in healthy pregnant women and hospital environments in Benin: an approach based on Tricycle - Sintondji, Kevin; Fabiyi, Kafayath; Hougbenou, Jules; Koudokpon, Hornel; Lègba, Boris; Amoussou, Hornella; Haukka, Kaisa; Dougnon, Victorien (Frontiers in Public Health, 2023)
Introduction Extended-Spectrum Beta-Lactamase (ESBL)-producing Enterobacterales are recognized as significant pathogens due to their resistance to multiple antibiotics. This study aimed to determine the prevalence of ESBL-producing Escherichia coli (E. coli) in different settings, including healthy pregnant women, the food chain, and the environment of tertiary hospitals in Benin. Methods Samples were collected from various sources, including fecal samples from healthy pregnant women, food samples from hospital canteens, and hospital effluents from four tertiary hospitals in southern Benin. Fecal samples were plated on MacConkey agar supplemented with cefotaxime (4 μg/mL), while food and water samples were plated on Tryptone Bile X agar supplemented with cefotaxime (4 μg/mL). Urea indole tests were used for preliminary identification of E. coli colonies, followed by confirmation of ESBL production using the double disk synergy technique. Antibiotic susceptibility testing of ESBL-producing E. coli strains was conducted using the disk diffusion method on MH agar. Polymerase Chain Reaction (PCR) was used to investigate the presence of ESBL-encoding genes. Results Among the 296 fecal samples collected from four tertiary hospitals, ESBL-producing E. coli was isolated from 22.30% (66) of the samples. All E. coli isolates from hospital effluents exhibited ESBL production, while ESBL-producing E. coli was not detected in food and drinking water samples. The analysis of variable associations showed no significant associations (p > 0.05) for the studied factors. Antibiotic susceptibility testing revealed high resistance rates among the ESBL-Ec isolates against several tested antibiotics, including amoxicillin, aztreonam, ceftriaxone, ciprofloxacin, and trimethoprim-sulfamethoxazole. However, most isolates remained susceptible to ertapenem, amoxicillin-clavulanate, and imipenem. The most prevalent ESBL-encoding genes were blaTEM (37.50%), blaOXA-1 (19.44%), and blaSHV (11.11%), while a smaller proportion of isolates carried blaCTXM-1/blaCTXM-15 (5.55%) and blaCTXM-9. Discussion This study provides insights into the prevalence of ESBL-producing E. coli carriage in the feces of healthy pregnant women in southern Benin. Additionally, it highlights hospital wastewater as a potential reservoir of ESBL-producing bacteria in the environment. The detection of ESBL-producing E. coli in hospital effluents raises concerns about the dissemination of antibiotic resistance genes into the environment. The high resistance rates observed among ESBL-Ec isolates against commonly used antibiotics emphasize the urgent need for antimicrobial stewardship and infection control measures. The identification of prevalent ESBL-encoding genes contributes to understanding the genetic basis of ESBL resistance in the studied population. Further research is warranted to explore the mechanisms of transmission and potential interventions to mitigate the spread of ESBL-producing Enterobacterales.